INDIVIDUALIZED MANAGEMENT STRATEGIES FOR VERY SEVERE HYPERTRIGLYCERIDEMIA: A CASE SERIES - Verasingam, Jaarvis; Victor, Selvan Lious; Rahmatullah, Ijaz Bt Hallaj; Rahim, Anilah Bt Abdul; Ng, Wei Wei (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Very severe hypertriglyceridemia (HTG) is defined by the Endocrine Society as a serum triglyceride concentration ≥22.6 mmol/L. Management typically involves dietary modification, pharmacotherapy such as fibrates combined with statins, insulin therapy, and plasmapheresis in select cases. We report two cases of non-familial very severe HTG secondary to poorly controlled type 2 diabetes mellitus, each managed using different therapeutic strategies. CASE Case 1: A 23-year-old female with type 2 diabetes mellitus and class I obesity (BMI 29.3 kg/m²) presented with diabetic ketoacidosis and acute pancreatitis. She had a history of poor adherence to insulin therapy. Her serum triglyceride level was markedly elevated at 64 mmol/L. She was treated with a fixed-rate intravenous insulin infusion (0.1 units/kg/hour) and kept on nothing per orem, resulting in a significant reduction of triglyceride levels to 2.5 mmol/L within three days. Case 2: An 83-year-old female with type 2 diabetes mellitus, stage 4 chronic kidney disease, hypertension, neurocognitive disorder and osteoporosis who was incidentally found to have severe HTG (25.6 mmol/L) during routine screening. Despite being asymptomatic, she was started on a variable-rate intravenous insulin infusion to reduce the risk of pancreatitis. Her triglyceride levels decreased to 16.8 mmol/L but then plateaued. Insulin was discontinued, and a low-carbohydrate, low-fat diet with intermittent fasting (from lunch until the next day’s breakfast) was initiated. This led to a reduction in her triglyceride level to 9.01 mmol/L within three days. Both patients were discharged with premixed insulin, rosuvastatin, omega-3 fatty acid supplementation and additional fenofibrate for Case 1 only, as Case 2 has CKD stage 4. CONCLUSION These cases highlight the importance of individualized treatment strategies in managing very severe non-familial HTG. While insulin infusion and dietary interventions were effective in both patients, the choice of therapy should be guided by clinical context.